Draft Annual Plan 2009-10 Union Territory of Chandigarh - Planning Commission (Planning Commission, 2009)
Stretching over an area of 114 sq. Kms., the Union Territory of Chandigarh has 13 Villages around the city. The Union Territory witnessed decennial population growth (1991-2001) of 44.33% and had a population of 9,00,914 in the last census. Chandigarh is unique, because it is the capital of two state governments, Punjab and Haryana. Chandigarh is a planned city, with a high standard of civic amenities. Chandigarh’s infrastructure was originally planned for a population of 5 lakh, but the city has expanded rapidly over the last three decades and faces problems common to other growing cities in India, including the proliferation of slums and squatter settlements. Despite these problems, Chandigarh ranks first in India in the Human Development Index, quality of life and e-readiness.
Finance Department Chandigarh Administration Planning & Evaluation Organisation